Effectiveness of Providing Galoba (Hornstedtia sp.) Fruit Tea on Glutathione Peroxidase Enzyme Activity in the Serum of Hyperglycemic Mice (Mus musculus) - Abdul Tuahena; Rachmawati Dwi Agustin; Dian Qisthi (Universitas Airlangga, Surabaya, Indonesia, 2026)
Background: Hyperglycemia leads to increased production of free radicals and reduced activity of endogenous antioxidant enzymes such as glutathione peroxidase (GSH-Px). Oxidative stress plays a crucial role in the progression of diabetes complications. Galoba fruit (Hornstedtia sp.) is a traditional herbal plant rich in flavonoids, recognized for its antioxidant properties. Objective: To evaluate the effect of galoba fruit tea on GSH-Px enzyme activity in the serum of hyperglycemic mice. Materials and Methods: This study used post-test-only control group design. Twenty-four male Balb/C mice were divided into six groups: CN (normal control), C- (negative control), C+ (positive control, receiving metformin 1.3 mg/kg BW), and three treatment groups receiving galoba fruit tea at doses of 100 mg/kg BW (T1), 200 mg/kg BW (T2), and 300 mg/kg BW (T3). Hyperglycemia was induced with multiple low doses of Streptozotocin (40 mg/kg BW) for 5 days. We collected serum on day 22, and measured GSH-Px activity using a UV–Vis Spectrophotometer at 412 nm. Results: Administration of galoba fruit tea increased GSH-Px activity, with the highest mean value observed in the T1 group (38.08 U/mL), followed by T2 (36.11 U/mL) and T3 (20.74 U/mL). However, these differences were not statistically significant (p > 0.05). Conclusion: Galoba fruit tea exhibits potential in enhancing GSH-Px enzyme activity in hyperglycemic mice, particularly at lower doses, demonstrating its capacity in supporting endogenous antioxidant defense mechanisms as a complementary strategy to manage hyperglycemia.